Data for: Predicting berry plant habitat under climate change in Bristol Bay, AK ... - Hamilton, Casey; Smithwick, Erica; Spellman, Katie; Baltensperger, Andrew; Spellman, Blaine; Chi, Guangqing (Zenodo, 2023)
Aim: Climate change is altering suitable habitat distributions of many species in high latitudes. Fleshy fruit-producing plants (hereafter "berry plants"), important in arctic food webs and as subsistence resources for human communities, may be impacted, but their response to a warming and increasingly variable climate at a landscape scale has not yet been examined. Here, we identified influential environmental determinants of berry plant distribution and produced predictions on how climate change might shift these distributions. Location: Bristol Bay and Togiak NRCS Survey Areas, Alaska. Methods: We built species distribution models using the Random Forests algorithm to identify key characteristics and predict the spatial distribution of habitats suitable for five berry plant species: Vaccinium uliginosum L., Empetrum nigrum L., Rubus chamaemorus L., Vaccinium vitis-idaea L., and Viburnum edule (Michx.) Raf. Then, we used future climate projections (2081-2100; representative concentration pathways 4.5, 6.0, ... : See README file for details. Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: 1927827Funding provided by: USDA National Institute of Food and Agriculture and Multistate Research Project* Crossref Funder Registry ID: Award Number: PEN04623Funding provided by: Eunice Kennedy Shriver National Institute of Child Health and Human Development Crossref Funder Registry ID: http://dx.doi.org/10.13039/100009633 Award Number: P2C HD041025Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: 2207436Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: 2032790 ...